2016
DOI: 10.1007/s10792-016-0185-8
|View full text |Cite
|
Sign up to set email alerts
|

Plasma adropin level in patients with pseudoexfoliation

Abstract: The aim of this study was to evaluate plasma adropin levels in patients with pseudoexfoliation (PEX). This retrospective case-control study included 35 patients with PEX and 35 individuals without PEX who served as controls. Plasma adropin levels with triglycerides, total cholesterol, low-density lipoprotein (LDL), high-density lipoprotein (HDL), and haemoglobin A1c (HGBA1C) concentrations were measured in both groups. The mean serum adropin levels were 3.24 ± 0.95 ng/mL (range, 1.90-7.88 ng/mL) in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The authors posited that these ratios may eventually be useful in predicting the progression to glaucoma in pseudoexfoliation patients, but a favorable sensitivity and specificity profile of such screening compared to current ophthalmic examination methods are yet to be demonstrated. It has also been recently reported that pseudoexfoliation patients have lower serum levels of adropin, a metabolic regulator that modulates glucose-mediated insulin release (30, 31). The implications and reproducibility of this association are unclear.…”
Section: Systemic Manifestationsmentioning
confidence: 99%
“…The authors posited that these ratios may eventually be useful in predicting the progression to glaucoma in pseudoexfoliation patients, but a favorable sensitivity and specificity profile of such screening compared to current ophthalmic examination methods are yet to be demonstrated. It has also been recently reported that pseudoexfoliation patients have lower serum levels of adropin, a metabolic regulator that modulates glucose-mediated insulin release (30, 31). The implications and reproducibility of this association are unclear.…”
Section: Systemic Manifestationsmentioning
confidence: 99%
“…Plasma adropin level has a positive association with severity of heart failure and negative correlation with left ventricular ejection fraction (Lian et al, 2011 ). Low level of plasma adropin is predictive of pseudoexfoliation (Oğurel et al, 2016 ), coronary slow flow phenomenon (Demircelik and Kurtul, 2015 ), saphenous vein graft occlusion following coronary artery bypass grafting (Demircelik, 2014 ), as well as pediatric obstructive sleep apnea in the presence of endothelial dysfunction (Gozal et al, 2013 ). While Gu et al ( 2015 ) described plasma adropin level as an independent indicator of hypertension, other studies failed to show this association (Altincik and Sayin, 2015 ).…”
Section: Introductionmentioning
confidence: 99%